2007
DOI: 10.1111/j.1600-0714.2007.00536.x
|View full text |Cite
|
Sign up to set email alerts
|

An updated clinical and epidemiological profile of the adenomatoid odontogenic tumour: a collaborative retrospective study

Abstract: This updated review based on the largest number of AOT cases ever presented, confirms the distinctive, although not pathognomonic clinicopathological profile of the AOT, its worldwide occurrence, and its consistently benign behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
164
7
14

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 147 publications
(206 citation statements)
references
References 91 publications
21
164
7
14
Order By: Relevance
“…It has been generally reported that AOT corresponds to 2.2-8.7 % of all odontogenic tumors [2,10,19]. However, in a worldwide collaborative retrospective study, the relative frequency of AOT ranged from 0.6 to 38.5 % [4]. Interestingly, the highest percentages were found in studies from Nigeria, which might suggest geographic differences in the frequency of these tumors [4].…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…It has been generally reported that AOT corresponds to 2.2-8.7 % of all odontogenic tumors [2,10,19]. However, in a worldwide collaborative retrospective study, the relative frequency of AOT ranged from 0.6 to 38.5 % [4]. Interestingly, the highest percentages were found in studies from Nigeria, which might suggest geographic differences in the frequency of these tumors [4].…”
Section: Discussionmentioning
confidence: 92%
“…However, in a worldwide collaborative retrospective study, the relative frequency of AOT ranged from 0.6 to 38.5 % [4]. Interestingly, the highest percentages were found in studies from Nigeria, which might suggest geographic differences in the frequency of these tumors [4]. Nonetheless, it must be emphasized that the recent inclusion of odontogenic keratocysts in the group of odontogenic tumors [20] may make in some instances a marked impact on the reported relative frequency of AOT [4].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations